2018
DOI: 10.1159/000486246
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Reperfusion Status after Intra-Arterial Thrombectomy for Prediction of Outcome in Anterior Circulation Large Vessel Stroke

Abstract: Background: Reperfusion status after intra-arterial thrombectomy (IAT) is a critical predictor of functional outcome after acute ischemic stroke. However, most prognostic models have not included a detailed assessment of reperfusion status after IAT. Objective: The aim of this work was to assess the association between successful reperfusion and clinical outcome. Methods: Clinical, radiological, and procedural variables of patients treated with IAT were extracted from our prospective stroke registry. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…Nevertheless, there is a strong correlation between successful reperfusion and patients' outcome, as shown in recent literature [9,10,19,40]. The study cohort is the same size as in other comparable studies.…”
Section: Limitationmentioning
confidence: 83%
“…Nevertheless, there is a strong correlation between successful reperfusion and patients' outcome, as shown in recent literature [9,10,19,40]. The study cohort is the same size as in other comparable studies.…”
Section: Limitationmentioning
confidence: 83%
“…Our study demonstrated that the effect of mTICI-3 reperfusion was not significantly modified by patients' baseline characteristics such as age, sex, NIHSS score, ASPECTS, and target occlusion location among patients www.nature.com/scientificreports www.nature.com/scientificreports/ with anterior circulation occlusion. Previous studies have reported the effect of complete reperfusion on outcomes [4][5][6][7][8][9][10][11][12][22][23][24] , but the heterogeneity of this effect according to patients' characteristics has not been fully investigated. Although the superiority of mTICI-3 reperfusion did not reach statistical significance in some subgroups, presumably due to insufficient power, our findings provide further support for the importance of achieving mTICI-3 reperfusion regardless of the baseline characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have previously investigated the relation between various eTICI scores and clinical outcome. [6][7][8][9][10] The results of these studies varied, which may be due to variations in definitions and the fact that some studies had a small sample size. [7][8][9][10] Moreover, some studies used clinical trial data, 6 which may not reflect daily clinical practice.…”
mentioning
confidence: 99%